Proposed Wastewater Treatment Plant for a Paper Mill - Ali, Arshad; Iqbal, Muhammad Jawed (Hydro Nepal: Journal of Water, Energy and Environment, 2012)
The decline in the availability and alarming pollution of the existing water resources is the major environmental problem of third-world countries. The main reason of water pollution is the disposal of untreated industrial effl uents. This study was designed to evaluate the pollution load caused by a paper mill, and to propose a wastewater treatment plant design, based on the analyses of wastewater samples. The wastewater samples were collected from the local paper mill for a period of more than four months on a regular basis. The pH, temperature, color, TSS, TDS, BOD, COD and AOX were measured as, 8.1, 23°C, 2,431 PtCo unit, 956 mg/L, 3,046 mg/L, 1,582 mg/L, 2,492 mg/L and 19.81 mg/L, respectively. Based on the data obtained, the wastewater treatment plant consisting of a screening chamber, primary sedimentation tank and a UASB reactor was designed. It was concluded that the treatment effi ciency of more than 75% removal of BOD and COD concentrations could be accomplished. The treatment plant will also be able to produce 2,200 m3/day of biogas. DOI: http://dx.doi.org/10.3126/hn.v11i0.7157 Hydro Nepal Vol.11 2011 pp.25-28